RELATED LEARNING MOTIVATION AND FACILITY STUDY AT HOME WITH ACHIEVEMENT EYES COOLING SYSTEM STUDENTS OF CLASS XI LIGHT VEHICLE ENGINEERING VOCATIONAL SCHOOL OF STATE 1 LIGHT SEDAYU BANTUL - Khoironi Taufik Prasetyo; Tarto Sentono (Universitas Sarjanawiyata Tamansiswa, 2014)
The purpose of the study was to determine (1) whether there is a positive relationship between learning motivation with learning achievement cooling system students of class XI Mechanical Light Vehicle Vocational School of State 1 Sedayu Bantul, (2) whether there is a positive relationship between learning facilities at home, with learning achievement cooling system students of class XI Mechanical Light Vehicle Vocational School of State 1 Sedayu Bantul, (3) to determine whether there is a positive relationship between learning motivation and learning facilities at home learning achievement cooling system students of class XI Mechanical Light Vehicle Vocational School of State 1 Sedayu Bantul.This research was conducted at Vocational School of State 1 Sedayu Bantul academic year 2013/ 2014 on July 22 till December 12, 2013. This study is a population so that all class XI Mechanical Light Vehicle Vocational School of State 1 Sedayu Bantul, made in the sample of 96 students. This research is correlational and ex post facto research is classified. Date collection using questionnaires and documentation. The validity of the items were obtained from the product moment correlation. Of 20 instruments fall motivation questionnaire 2, and 30 facilities in the questionnaire instruments fall 6. About the reliability of the formula obtained by alpha, motivation rtt 0.493 and 0.709 and facilities declared reliable. Before the date were analyzed first tested the normality test is prerequisite analysis, independent test, and linearity test. Analysis of data using simple regression analysis and multiple regression analysis.From the analysis of the date obtained the following results: (1) There is a positive and significant relationship between learning motivation (X1) with learning achievement of cooling system (Y), (2) There is a positive and significant relationship between learning facilities at home (X2) with learning achievement cooling system (Y), (3) learning motivation (X1) and learning facilities at home (X2) jointly have a positive and significant relationship together with learning achievement of cooling system (Y).